Speaking out loud: Muslim women, Indian Delights and culinary practices in eThekwini/Durban - Wardrop, Joan (Routledge and Centre for African Studies, University of Cape Town, 2012)
I asked, 'Did your mother teach you to cook?' Almost an hour later, time consumed by mutual reminiscences of Indian Delights, stories of the tastes and textures and colours of food and life in Durban, at last when I thought it would never be answered my question swam back up to the surface of our conversation: 'You know, then I lived with my oldest sister, not my mother. Her mother-in-law taught me.' Too heavy a shift of register, the answer dropped into the bubble of conversation we had made around ourselves, imposing another reluctant silence. I could not ask more, not then. Deliverance came through other stories. We talked about the subtly different combinations of spices that women even from the same family choose to use, and the embodied pleasures of walking into a kitchen steamed up with the smells of several dishes all cooking at once. And for the moment we avoided returning to a family narrative of separation, loss and melancholy.